2021
DOI: 10.1038/s41598-021-84331-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of tumor hypoxia and perfusion in recurrent glioblastoma following bevacizumab failure using MRI and 18F-FMISO PET

Abstract: Tumoral hypoxia correlates with worse outcomes in glioblastoma (GBM). While bevacizumab is routinely used to treat recurrent GBM, it may exacerbate hypoxia. Evofosfamide is a hypoxia-targeting prodrug being tested for recurrent GBM. To characterize resistance to bevacizumab and identify those with recurrent GBM who may benefit from evofosfamide, we ascertained MRI features and hypoxia in patients with GBM progression receiving both agents. Thirty-three patients with recurrent GBM refractory to bevacizumab were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…They found long-term survivors of GBM (>36 months) tend to have slow-growing diffuse tumors with high T1-contrast and high FLAIR signal, whereas short-term survivors (<19 months) tend to have fast-growing focal tumors with little FLAIR signal [5,6]. Huang and colleagues recently demonstrated small hypoxic tumors display little FLAIR signal and correlate with poor outcome, confirming Swanson's work [5][6][7]. The switch from aerobic to anaerobic respiration in cancers results from elevation of active hypoxia-inducible factor 1α (HiF) levels [8].…”
Section: Introductionmentioning
confidence: 82%
“…They found long-term survivors of GBM (>36 months) tend to have slow-growing diffuse tumors with high T1-contrast and high FLAIR signal, whereas short-term survivors (<19 months) tend to have fast-growing focal tumors with little FLAIR signal [5,6]. Huang and colleagues recently demonstrated small hypoxic tumors display little FLAIR signal and correlate with poor outcome, confirming Swanson's work [5][6][7]. The switch from aerobic to anaerobic respiration in cancers results from elevation of active hypoxia-inducible factor 1α (HiF) levels [8].…”
Section: Introductionmentioning
confidence: 82%
“…Subsequently, tumor vasculature is functionally abnormal with markedly increased interstitial fluid pressure, aggravating hypoxia and acidosis [ 173 ]. Under such conditions, radiations are less effective because of the hypoxic environment, while drug delivery is dramatically impeded [ 20 , 174 , 175 , 176 ]. This has given birth to the concept of vessel normalization, a strategy aiming to reduce hypoxia, improve drug distribution, and restore immune cell infiltration ( Figure 3 ) [ 177 ].…”
Section: Gbm Resistance To Anti-angiogenic Therapiesmentioning
confidence: 99%
“…Studies have demonstrated the important role of advanced MRI sequences, including DSC-MRI and DWI, in tumor grading, treatment effect prediction, and evaluation of disease progression in patients with glioma. [1][2][3][4][5][6][7][8][21][22][23][24] The protocol employed by these studies included pretreatment MRI alone, posttreatment MRI alone, and both pre-and posttreatment MRI. Studies that analyzed pretreatment MRI did not often specify whether MRI acquisition was performed before biopsy.…”
Section: Discussionmentioning
confidence: 99%